Réponses

2014-02-27T13:12:53+01:00
C = (6√2)² + 1
= 36 ×2 +1
=  72 + 1 = 73 

D = ( 3- √5)² -2 (1- √45)
= 9 -6√5 + 5 - 2 (1- √45)
= 14 - 6√5 -2 + 2√45
= 12 -6√5 +2×3√5 
= 12 -6√5 +6√5 
=12 - √5

3√24 +√54 - √96
= 3* 4√6 + 3√6 - 4√6
= 12√6 + 3√6 - 4√6
= 9√6

A =7/9 + 2 - 2 ×3 = 7/9 +  4 = 7/9 + 2 = 9/9 = 1
              3-3 × 7             18            9

B = ( -2) ×10⁻³ ×25 ×(10²)²  =    ( -2)     ×   10⁻³×10⁴ = 10 ×10⁻¹ = 1
       50× 10⁵ × (-0.1)×10⁻³      2×(-0.1)           10²

C = 3√96 = 3×4√6√6 = 1
      4√54    4×3√6    √6


Au plaisir de t'avoir aidé